STRATEGI KOMUNIKASI PERIKLANAN BELOW THE LINE (BTL) PT AGHNA (KREANOVA), BANDUNG DALAM MENJALANKAN BISNIS PRINT AD - Agustrijanto, Agustrijanto (JURNAL KOMUNIKATIO, 2022)
Today the use of advertising in the below-the-line (BTL) media is a big question about the effectiveness and benefits, whether financial and branding corporate, because they are considered outdated, unfavorable, and does not represent the dynamics of digital advertising. On the other hand, digital advertising development has become a trend investor the essential advertising business seen as business advertising. This caused some parties to be sceptical of the company advertising classic BTL, significantly relying on below-the-line orders. Aghna (Kreanova) in Bandung is one of the company’s advertisings concerned with their business advertising in BTL, in the fight business competition advertising, which is moving toward the digital. This study used a qualitative approach to describe the phenomenon of advertising. Aghna (Kreanova) maintains a venture and concept product marketing BTL by combining a marketing approach with the advertising concept that emphasizes marketing strategies. It means of promoting a product BTL with the approach direct selling is still in use to improve the gain on sale of the corporate and existence.